Synthesis and Characterization of Mn(II),VO(II) and UO2(II) Complexes with Schiff Base Derived from 2-Hydroxy Naphthaldehyde and 4,4´-Diaminodibenzyl - A. FILMWALA, ZOEB; M. NANDAVADEKAR, SANJAY; M. PATIL, RAJU (Asian Journal of Chemistry, 2010)
In the present studies, the complexes of Mn(II), VO(II) and UO2(II) prepared from Schiff base have been reported. The Schiff base derived from 2-hydroxy naphthaldehyde and 4,4'-diaminodibenzyl. The Schiff base and metal complexes characterized by elemental analysis, molar conductance, 1H NMR, IR, electronic spectra, magnetic susceptibility studies. The spectral data suggests octahedral structure for Mn(II) and UO2(II) complexes and square pyramidal for VO(II) complex.